2017
DOI: 10.3389/fpls.2017.00419
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Overgrazing-Induced Memory Decreases Photosynthesis of Clonal Offspring in a Perennial Grassland Plant

Abstract: Previous studies of transgenerational plasticity have demonstrated that long-term overgrazing experienced by Leymus chinensis, an ecologically dominant, rhizomatous grass species in eastern Eurasian temperate grassland, significantly affects its clonal growth in subsequent generations. However, there is a dearth of information on the reasons underlying this overgrazing-induced memory effect in plant morphological plasticity. We characterized the relationship between a dwarf phenotype and photosynthesis functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 66 publications
11
39
0
Order By: Relevance
“…Five years fencing significantly improved the photosynthetic capacity in both species. In addition, fencing increased the daily mean P N values in both species, which is consistent with the previous research (Zhang et al, 2009;Zlatev and Fernando, 2012;Tao et al, 2015;Ren et al, 2017). However, the patterns of P N under both regimes varying across the three observation dates were different in E. nutans and P. anserina, which was likely attributed to the different adaptions of the two species.…”
Section: Discussionsupporting
confidence: 90%
“…Five years fencing significantly improved the photosynthetic capacity in both species. In addition, fencing increased the daily mean P N values in both species, which is consistent with the previous research (Zhang et al, 2009;Zlatev and Fernando, 2012;Tao et al, 2015;Ren et al, 2017). However, the patterns of P N under both regimes varying across the three observation dates were different in E. nutans and P. anserina, which was likely attributed to the different adaptions of the two species.…”
Section: Discussionsupporting
confidence: 90%
“…With the increase of grazing intensity, in order to better adapt to grazing, plants not only change morphological indicators but also change physiological indicators such as photosynthesis and redistribution of nutrients in plants [28,29]. Grazing reduces the leaf area of plants, directly affects photosynthesis [30], and even directly impairs some functions of plants [31]. In addition, grazing can affect the water situation in plants, thus changing the relationship between net photosynthetic rate and water, leading to the decline of net photosynthetic rate [30].…”
Section: Instructionmentioning
confidence: 99%
“…Grazing reduces the leaf area of plants, directly affects photosynthesis [30], and even directly impairs some functions of plants [31]. In addition, grazing can affect the water situation in plants, thus changing the relationship between net photosynthetic rate and water, leading to the decline of net photosynthetic rate [30]. However, many studies have found that moderate grazing and mowing can stimulate plants to produce compensatory growth, thus restoring their lost biomass, and even produce more biomass.…”
Section: Instructionmentioning
confidence: 99%
“…L. chinensis is a perennial herb, which is one of the favorite forages of large herbivores because of its high palatability and proper nutritional values [4]. However, long-term livestock farming, dominated by sheep and goats, causes severe degradation by reducing canopy cover significantly [5]. Therefore, alternative forage sources are needed as a substitute for L. chinensis to reduce grassland degradation dominated by L. chinensis and to alleviate vacancies in high-quality forage.…”
Section: Introductionmentioning
confidence: 99%